2023
DOI: 10.3390/bioengineering10070772
|View full text |Cite
|
Sign up to set email alerts
|

Hallux Limitus Influence on Plantar Pressure Variations during the Gait Cycle: A Case-Control Study

Claudia Cuevas-Martínez,
Ricardo Becerro-de-Bengoa-Vallejo,
Marta Elena Losa-Iglesias
et al.

Abstract: Background: Hallux limitus is a common foot disorder whose incidence has increased in the school-age population. Hallux limitus is characterized by musculoskeletal alteration that involves the metatarsophalangeal joint causing structural disorders in different anatomical areas of the locomotor system, affecting gait patterns. The aim of this study was to analyze dynamic plantar pressures in a school-aged population both with functional hallux and without. Methods: A full sample of 100 subjects (50 male and 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Due to the novelty of this topic, a discussion is difficult due to the impossibility of comparing our results with those of other studies using the OptoGait system. Some case-control studies have shown that the presence of HL, structural or functional, causes the maximum plantar pressure under the hallux to accumulate more significantly and at a faster rate than in the first metatarsal head, with a consequent increase in pressure in the rest of the forefoot [1,3]. Dananberg affirmed that the limitation in hallux movement in the propulsive phase of gait, when repeated thousands of times daily, does not only alter foot and postural biomechanics, but also causes and perpetuates many chronic postural alignments, including lower back pain [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the novelty of this topic, a discussion is difficult due to the impossibility of comparing our results with those of other studies using the OptoGait system. Some case-control studies have shown that the presence of HL, structural or functional, causes the maximum plantar pressure under the hallux to accumulate more significantly and at a faster rate than in the first metatarsal head, with a consequent increase in pressure in the rest of the forefoot [1,3]. Dananberg affirmed that the limitation in hallux movement in the propulsive phase of gait, when repeated thousands of times daily, does not only alter foot and postural biomechanics, but also causes and perpetuates many chronic postural alignments, including lower back pain [2].…”
Section: Discussionmentioning
confidence: 99%
“…During gait, the body structure is designed to pull the centre of mass to a single pivot point formed by the dorsiflexion of the first metatarsophalangeal joint (MPJ). Various studies have studied how structural and functional modifications of the MPJ can modify normal ambulation [ 1 , 2 , 3 ]. There is no scientific evidence to highlight whether the limitation of the hallux range of motion (ROM) alters spatiotemporal gait parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation